Aksi Bersih Pantai Sebagai Upaya Menjaga Kebersihan Lingkungan Dikawasan Pantai Falajawa Kota Ternate - Unkhair, Firman; Yetty; Octasary, Magvirah; Widyawasti Anwar, Indry; Hi Muhammad, Hujaefa; Jusnita, Naniek (Program Studi Kehutanan, Universitas Khairun, 2024)
Garbage is one of the problems faced by the people of Ternate City. One of solution to encourage people to care about the environment is by conducting socialization and beach clean-up activities. Thus, the lecturers of the English Language Education Study Program collaborated with the North Maluku Regional Police, students and the community conducted community service with the theme